Вы находитесь на странице: 1из 2

# CHAPTER 2: FREE VIBRATIONS OF SINGLE DEGREE OF FREEDOM

SYSTEM
1. Free Vibration Of An Undamped Translational System

() = 1 + 2 (8)

= /2 (16)
And the natural period is:

= 2/ = 1 (17)

## Eq. (8) can be written as:

() = 1 cos( ) + 2 sin( ) (9)
Appling the initial conditions at t=0 to Eq. (9) yields:
( = 0) = 1 = 0
( = 0) = 2 = 0 (10)
Thus the solution of Eq. (3) subject to the initial conditions

+ = () (1)

## This system is vibrating about its equilibrium state freely (no

external forces acting, only an impulse to cease equilibrium, that is:

notation:

() = 0 (2)

1 =

## 2. Free Vibrations Of An Undamped Torsional System

The only difference between the translational and torsional systems
is that the mass element in the translational system is replace by
the mass inertia in the torsional system. So Eq. (3) can be rewritten
as:

2 = (12)

So,
+ = 0 (3)

+ = 0 (18)

## Where and A are the new constants, which can be expressed in

terms of 1 and 2 .

() =

(4)

= =

12

## Substituting Eq. (4) into (3) gives:

2

( + ) = 0 (5)
Since C cannot be zero, we have:
2 + = 0 (6)

12

02

0
+ ( )2

= = 1 (2 ) = 1 (
1

0
0

) (13)

Introducing Eq. (12) into Eq. (8), the solution can be written as:
() = cos( + ) (14)
Where is the natural frequency of any system.

And hence:

= = (7)
The general solution of Eq. (3) can be expressed as:

= = (15)
The natural frequency in cycles per second is given by:

## And so on for the rest.

3. Free Vibrations Of Damped System
The difference between the damped system and the undamped
system is only the dampening element that constrain the vibration.
Hence the damper dissipates the vibratory system energy by
applying some sort of friction (viscous or coulomb).

## Thus the equation of motion becomes:

+ + = 0 (19)
The solution of Eq. (19) can be found by the assumption made in
equation (4).

The nature of the s1 and s2 and hence the behavior of the solution,
Eq. (27) depends on the magnitude of damping. From that we can
recognize 4 cases.

## And by applying the same initial conditions which were applied in

case 3, C1 and C2 are:

## *Case 2: Underdamped system ( < 1), the damping frequency is:

And then Eq. (6) can be written as:
= 1 2 (28)

2 + + = 0 (20)

1,2 =

1 =

## And the hence the root for Eq. (20) is:

2 4

( ) = 1 ( +

() = cos(1 2 ) ) (29)

2 =

2 1)

## The roots give two solution to Eq. (19):

1 () = 1 1 2 () = 2 2 (22)

+ 2 (

2 1)

(34)

0 ( + 2 1) + 0
2 2 1

0 ( 2 1) 0
2 2 1

(21)
Where is the amplitude and is the phase angle, and they are
determined from the initial conditions.

## Eq (34) shows that the motion is aperiodic regardless of the initial

conditions imposed on the system. Since roots s1and s2 are both
negative, the motion diminishes exponentially with time, as shown
in Figure below that compares the 4 cases.

Damping
envelope

## Thus the general solution of Eq. (19) is given by a combination of the

two solutions from Eq. (22):
() = 1 1 + 2 2

( ) = 1

+24

+ 2

2 4

## In damped vibrations, it is of a great significance to define the terms

related to the damping.

## And the solution is:

= 2 = 2 = 2 (24)
The damping ratio is defined as the ratio of the damping constant
to the critical damping constant:
= (25)

+ 2 (

2 1)

## The application of the initial conditions ( = 0) = 0

( = 0) = 0 gives 1 = 0 2 = 0 + 0 and the
solution becomes:

## *Case 4: Overdamped system ( > 1) that the roots s1 and s2 are

real and distinct and are given by:

1,2 = ( 2 1) (26)

() = (1 + 2 ) (31)

() = [0 + ( 0 + 0 )] (32)

And hence Eq. (21) and Eq. (22) can be written as:

2 1)

## *Case 3: Critically damped ( = 1), in critically damped systems the

roots are identical, that is:

1 = 2 = 2
= 2 (30)

## The critical damping constant :

( ) = 1 ( +

Eq. (29)

(23)

(27)

1,2 = (( ( 2 1) (33)

4. Logarithmic decrement:
The logarithmic decrement represents the rate at which the
amplitude of a free-damped vibration decreases. It is defined as
the natural logarithm of the ratio of any two successive
amplitudes.

1
2

= =

(35)

= 2

1 (36)

## It is also possible to write the damping ratio as a function of the

logarithmic decrement:

(2)2 + 2

(37)